Sustainable Urban Housing in China Principles and Case Studies for Low-Energy Design - Glicksman, Leon.; Lin, Juintow; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
There is increasing attention to the need to preserve and improve the global environment for current and future generations. This book summarizes new research done in this area based on a number of important collaborative projects in Beijing, Shanghai and Shenzhen, China. Sustainable Urban Housing in China features case studies and recommendations for new approaches to environmentally responsive sustainable building. It illuminates many principles of sustainability and energy efficiency applicable to buildings throughout the world, and in developing countries in particular. These projects identify practical new and existing technologies that will enable designs to provide energy-efficient, healthy, and comfortable conditions. Individual chapters treat aspects of sustainable design including ventilation, controls, materials, and daylighting; design guidelines and organizational methods used in urban projects are also discussed.
Background -- Sustainability and the Building Sector -- China - Environment and Culture -- Design Principles -- Design Principles for Sustainable Urban Housing in China -- Materials and Construction for Low-Energy Buildings in China -- Technical Findings -- Low-Energy Building Design -- Wind in Building Environment Design -- Design of Natural Ventilation with CFD -- Light and Shading -- Case Studies -- Case Studies -- Case Study One - Beijing Prototype Housing -- Case Study Two - Beijing Star Garden -- Case Study Three - Shanghai Taidong Residential Quarter -- Case Study Four - Shenzhen Wonderland Phase IV -- Case Study Five - Beijing Hui Long Guan -- Future Steps -- Future Steps.
Keywords: ENGINEERING; HOUSING; ARCHITECTURE; MECHANICAL ENGINEERING; ENVIRONMENTAL SCIENCES; ENGINEERING; MECHANICAL ENGINEERING; HOUSING; ARCHITECTURE, GENERAL; CITIES, COUNTRIES, REGIONS; ENVIRONMENT, GENERAL